Pengaruh Kepribadian Proaktif dan Motivasi Berprestasi Terhadap Inovasi Guru Sekolah Minggu Buddha Se-Propinsi DKI Jakarta - Sudar Sudar (Sekolah Tinggi Agama Buddha Nalanda, 2023)
Learning innovation requires teacher attention to achieve optimal student learning outcomes. A professional teacher is expected to be able to carry out learning innovations that are manifestasi in his tasks everyday, both in lesson planning, implementation of the learning process to evaluation activities. This study aims to examine the effect of proactive personality on SMB teacher innovation, the effect of achievement motivation on SMB teacher innovation, and the effect of proactive personility and achievement motivasion together on SMB teacher inovation. Research using quantitative research methods. The sample use 142 respondents with data collection techniques through a questionnaire (close questionnaire) using a Likert Scale. The results of research on proactive personality have a significant effect on SMB teacher innovation. Achievement motivationhas a significant effect on SMB teacher innovation. While the results of research on proactive personlity and achievement motivation simulataneously have a significant effect on SMB teacher innovation. In conclusion, the higher the proactive personality and achiemevent motivation, the higher the innovatioan of SMB teachers.